MODEL SISTEM PENDUKUNG KEPUTUSAN (SPK) TINGKAT KEPUASAN KONSUMEN TRANSPORTASI ONLINE: Array (Universitas Harapan Medan, 2019)
Transportation is the process of transferring people or goods using vehicles driven by humans or machines. The switching of conventional transportation user services to online transportation is influenced by the sophistication of communication tools (technology) and the desires of the people who always want convenience. GoJek and Grab is an online application to provide transportation services that are currently growing very rapidly in Indonesia and are starting to emerge with several other similar applications that offer various advantages, so that competition is increasingly competitive. Good public transportation must meet three basic criteria: comfort, safety and accuracy. Determining the level of customer satisfaction are five factors: product quality, price, service quality, emotional and convenience. This research is to make a model of Decision Support System (SPK) which is used to help online transportation to know the level of customer satisfaction based on the answers of the questionnaire. The right selection will run effectively and the consumers will be satisfied. The proposed multi-criteria selection model is expected to help consumers identify the best transportation.